THE BIBLICAL PRINCIPLES AND IMPLICATIONS OF MISSION IN THE LIFE OF PAUL ON DEALING WITH THE CORONAVIRUS PANDEMIC - Warouw, Winda Novita (Klabat Theological Review; Vol 3 No 2 (2022): Klabat Theological ReviewDO - 10.31154/ktr.v3i2.889.106-115, 2022)
Through this study missiological of the biblical record, it is proved that: (1) The church is not immune to the challenges surfaced during the pandemic especially in evangelism; (2) There are biblical perspectives that can be implemented in mission for instance, before his repentance, Paul was a passionate man which indicates a passion that should be possessed by the mission workers today and, after his repentance Paul showed his consistency in his eagerness and the theme in his theology is the mission to the gentiles based in Christ’s love; and (3) There is a couple of practical implications found in this research: (a) Paul was able to be confident in all kinds of people which indicate that the present-day missionaries should be acquainted with the people that they’re going to reach; (b) Just as Paul encountered small and huge problems, the various challenges resulted by the pandemic should be overcome by the mission workers today; (c) It is evident through Paul’s ministry that challenges doesn’t always come from the outside of the church, therefore, the issues from the inside the church should be addressed in mission today during the pandemic; (d) Lastly, it is important to base any efforts of mission today on the Bible only as did Paul in his ministry. Keywords: Mission, Pandemic .